Organic Dissection of the Purported Ideological Benefits with the Help of Daksh Tyagi’s Text A Nation of Idiots (International Journal of Food and Nutritional Sciences, 2022)
This paper critiques the social and cultural biases in the political world with the help of the book An Indian Citizens Guide on How to Avoid A Nation of Idiots by Daksh Tyagi. The dichotomy of the political world exhibits many barricades leading to the subordination of one section of the society. The paper analyses how the state establishes its hegemony and brings up the issues to the upfront that are at the periphery. Arguing that the common people consume what media houses propagate and believe it to be true as Antonio Gramsci asserted that hegemony establishes with the consent of the people.